Root Silicon Addition Induces Fe Deficiency in Cucumber Plants, but Facilitates Their Recovery After Fe Resupply. A Comparison With Si Foliar Sprays - Hernández-Apaolaza, Lourdes; Escribano, Laura; Zamarreño, Ángel Mª; García-Mina, José Mª; Cano, Carlos; Carrasco-Gil, Sandra (Frontiers in Plant Science, 2020)
Silicon has not been catalogued as an essential element for higher plants. However, it has shown beneficial effects on many crops, especially under abiotic and biotic stresses. Silicon fertilization was evaluated for the first time on plants exposed to fluctuations in an Fe regime (Fe sufficiency followed by Fe deficiency and, in turn by Fe re-supply). Root and foliar Si applications were compared using cucumber plants that were hydroponically grown in a growth chamber under different Fe nutritional statuses and Si applied either to the roots or to the shoots. The SPAD index, Fe, and Mn concentration, ROS, total phenolic compounds, MDA concentration, phytohormone balance, and cell cycle were determined. The results obtained showed that the addition of Si to the roots induced an Fe shortage in plants grown under optimal or deficient Fe nutritional conditions, but this was not observed when Si was applied to the leaves. Plant recovery following Fe resupply was more effective in the Si treated plants than in the untreated plants. A relationship between the ROS concentration, hormonal balance and cell cycle under different Fe regimes, and in the presence or absence of Si was also studied. The contribution of Si to this signalling pathway appears to be related more to the induction of Fe deficiency, than to any direct biochemical or metabolic processes. However, these roles could not be completely ruled out because several hormone differences could only be explained by the additon of Si.